PEMANFAATAN TOGGLE SEBAGAI PENGGERAK MESIN PERAJANG KERUPUK TANPA ENERGI LISTRIK - Nugroho, Aris Adi; Syaifudin, Mukhamad; Fahlevi, Rizqi Rizal; Lubis, Achmad Zarkasi; Santoso, Eko Budi (Program Kreativitas Mahasiswa - Teknologi, 2013)
With the increasing production of crackers, entrepreneurs always face the problem of high operating costs rising rates electricity , so that employers re-use manual. Utilization toggle as the driving engine crackers chopper is a solution to reduce operational costs, increase capacity and quality of chopping. Observation, testing and prototyping is a method to determine the resolution of the problem, determine the number of blades and toggle the appropriate length and reduces the error rate. Machine dimensions 1010x410x850 mm using 80 pieces a knife with a long 965 mm 252 kg chopping crackers within 1 hour.